Business intelligence in non–profit organisations: Role of business intelligence in portuguese non-profit organisations to support decision-making and strategic definition - Carriço, Diogo Miguel Pereira (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence